Development of a LAMP method for detection of carbapenem-resistant Acinetobacter baumannii during a hospital outbreak - Carolina Garciglia Mercado; Ramon Gaxiola Robles; Felipe Ascencio; Jesus Silva-Sanchez; Maria Teresa Estrada-Garcia; Gracia Gomez-Anduro (Journal of Infection in Developing Countries)
Introduction: Carbapenem-resistant A. baumannii (CRAB) represents a public health threat increasing worldwide. We assess the suitability of a loop-mediated isothermal amplification (LAMP) method for on-site screening of CRAB in a hospital facility.